Antecedents of Green Purchase Behaviour: An Examination of Moderating Role of Green Wash Fear. (April 2016) - Rejikumar, G.
This study was designed to examine the effect of customer perceived green wash fear on certain critical antecedents that develop green purchase intentions among customers. The major antecedents such as customer perceived eco-literacy, perceived individual benefits, perceived customer effectiveness and perceived customer social responsibility were identified from prior empirical evidence. The skepticism in the minds of the customer about green claims was demonstrated by verifying the moderating role of perceived green wash fear on development of green purchase behaviour. The constructs in this study were conceptualized as reflective or formative based on theoretical considerations. A cross-sectional study was conducted in which perceptions of 188 retail customers from Cochin area in Kerala state of India were collected using a structured questionnaire. Variance-based structural equation modelling was used to analyze the linkage among variables of importance. The study found that, other than perceived customer effectiveness, all other variables significantly developed green purchase intentions. The perceived green wash fear was found to be significantly moderating all significant antecedents in the theoretical framework. The study concluded that for sustainable development, green-wash practices should be curbed effectively and customers should be properly and correctly informed about green properties of the products.